Modelo estocástico para dados GNSS e séries temporais de coordenadas GNSS - Marques, Heloísa Alves Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Functional models related to GNSS observations are better known than the stochastic models because the development these last one is more complex. Generally, stochastic models are applied in a simplified form, as the standard model, which assumes that all GNSS measurements have the same variance and are statistically independent, spatially and temporally. However, this assumption does not reflect the reality. Therefore, currently the stochastic models have been investigated more deeply, for instance, considering time correlation, ionospheric scintillation, among others. Brazil is located in the equatorial geomagnetic region and because of this suffers strong influence of ionospheric scintillation and other effects related to the ionosphere. Considering the recent technology of the GNSS receivers, that provide ways to obtain parameters of ionospheric scintillation, this effect is feasible of being considered in the stochastic modeling. Even if an adequate stochastic modeling could be applied in the GNSS data processing, it still may remain non-modeled errors (noise) that can influence the coordinate’s time series, especially those related to factors that go beyond the duration of one day, which is in general the interval (one day) used in the modeling and data processing. Thus, such noise can be characterized from the noise variance components of the time series. Therefore, this research aimed to expand the investigations regarding the stochastic modeling of GNSS observations mainly considering the ionospheric scintillation effects in the Brazilian region. Furthermore, it also aims to perform investigations related to methodologies for the noise characterization in the GNSS coordinates time series and establish a methodology for building functional models of these series...

Os modelos funcionais relacionados com as observações GNSS são mais conhecidos do que os modelos estocásticos, visto que o desenvolvimento destes últimos é mais complexo. Normalmente, utilizam-se modelos estocásticos numa forma simplificada, como o modelo padrão, o qual assume que todas as medidas das observações GNSS têm a mesma variância e são estatisticamente independentes, espacialmente e temporalmente. Porém, tal suposição não reflete a realidade. Desta forma, atualmente os modelos estocásticos vêm sendo pesquisados com maior profundidade, por exemplo, considerando correlação temporal, cintilação ionosférica, dentre outros. O Brasil, por estar numa região geomagnética equatorial, sofre forte influência de cintilação ionosférica e outros efeitos relacionados à ionosfera. Tendo em vista a recente tecnologia de receptores GNSS que proporciona a possibilidade de se obter parâmetros de cintilação ionosférica, este efeito é factível de ser considerado na modelagem estocástica. Mesmo com a realização de uma modelagem estocástica adequada no processamento de dados GNSS, ainda podem restar erros não-modelados (ruídos), os quais devem contaminar as séries temporais das coordenadas obtidas com as observáveis GNSS, em especial aqueles relacionados com fatores que extrapolam a duração de uma dia, que é o período em geral utilizado na modelagem e processamento dos dados. Desta forma, tais ruídos podem ser caracterizados a partir das componentes de variância dos ruídos das séries temporais. Sendo assim, essa pesquisa teve como objetivo expandir as investigações com relação à modelagem estocástica das observações GNSS considerando principalmente os efeitos de cintilação ionosférica na região brasileira...
Keywords: Cartografia; Modelagem de dados; Análise estocástica; Análise de séries temporais; Cintiladores; Sistema de Posicionamento Global; Cartography